2022
DOI: 10.1177/19485506211057976
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensions of American Conservative Political Orientation Differentially Predict Negativity Bias and Satisfaction With Life

Abstract: Numerous studies have linked political conservatism with negativity bias, whereas others have linked conservatism with indicators of positive adjustment. This research sought to reconcile this seeming contradiction by examining whether distinct dimensions of conservatism differentially predicted measures of negativity bias and positive adjustment. In two studies, we used an empirically derived and validated Attitude-Based Political Conservatism (ABPC) Scale that captures three correlated but distinct factors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Furthermore, past findings suggest that conservatives overall were more pathogen‐averse (Inbar et al., 2012). However, recent studies found negative associations between LI and pathogen aversion (Xu et al., 2022). Thus, conservatives higher in LI may be less bothered by the contamination/pathogen aspect of the pandemic compared to other conservatives.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, past findings suggest that conservatives overall were more pathogen‐averse (Inbar et al., 2012). However, recent studies found negative associations between LI and pathogen aversion (Xu et al., 2022). Thus, conservatives higher in LI may be less bothered by the contamination/pathogen aspect of the pandemic compared to other conservatives.…”
Section: Discussionmentioning
confidence: 97%
“…Higher LI is characterized by decreased support for government‐funded programs, and preferring minimal government interference (Xu et al., 2022). These individuals are less likely to support government restrictions to their daily lives, which may extend to the COVID‐19 safety precaution measures, especially government mandates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations